Assessment of Endometritis in Arabian Mare - Hamouda, MA; Al-Hizab, FA; Ghoneim, IM; Al-Dughaym, AM; Al-Hashim, HJ (ANIMAL PRODUCTION, 2012)
This study aimed to employ different methods for diagnosis of endometritis in Arabian mare. The study was conducted on 88 barren Arabian mares. After establishing the breeding history and completing the clinical examination, 50 of them were diagnosed as endometritis. Two swabs were obtained for bacteriological culture and cytological smears. Biopsy specimens were taken from the endometrium for histological examination. The results revealed that the ageing and the abnormal vulvar conformation were predisposing factors for endometritis. The number of mares affected with endometritis were 10, (20%) 13 (26%) and 27 (54%) in nullipara, primipara and pluripara mares respectively. Mares affected with endometritis were 6 (12%), 20 (40%), 18 (36%) and 6 (12%) in relation to body scoring 1, 2, 3 and 4 respectively. Bacteriological and mycological examinations of the uterine culture were positive in 41 (82%) and in 5 (10%) animals respectively. No growth was recorded in 4 swabs (8%). Â Streptococcus equi zooepidemicus were found to be the most common potential uterine bacterial pathogens (39.1% ) followed by E coli (21.7%). Cytological examination was positive in 60% (n=30) and negative in 40 % (n=40). The histopathological investigation revealed that 10/50 cases (20%), 18/40 cases (45.0%), 11/40 cases (27.5%), 7/40 cases (17.5%) and 4/40 cases (10.0%) were diagnosed as normal endometrium (Grade I), mild endometritis (Grade II A), moderate endometritis (Grade II B), severe endometritis (Grade III) and uterine atrophy respectively.Keywords: Arabian mare, biopsy, cytology, endometritisÂ Animal Production 14(2):99-103